2010
DOI: 10.1083/jcb.201006151
|View full text |Cite
|
Sign up to set email alerts
|

Elm1 kinase activates the spindle position checkpoint kinase Kin4

Abstract: Elm1 phosphorylates a conserved residue within the Kin4 kinase domain to coordinate spindle position with cell cycle progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(126 citation statements)
references
References 72 publications
8
117
0
1
Order By: Relevance
“…Thus, loss of Dma proteins does not seem to affect the whole polarisome. We previously showed that dma1D dma2D mutant cells are defective in the recruitment to the bud neck of the Elm1 kinase (Merlini et al 2012), which in turn is involved in septin organization, timely mitotic entry, and the checkpoint responding to spindle mispositioning (Sreenivasan and Kellogg 1999;Bouquin et al 2000;Thomas et al 2003;Gladfelter et al 2004;Caydasi et al 2010;Moore et al 2010). Artificial tethering of Elm1 to the bud neck by the Bni4-Elm1D420 chimeric protein (Moore et al 2010) significantly rescued the septin and spindle position defects of dma1D dma2D cells (Merlini et al 2012).…”
Section: Dma1 and Dma2 Are Required For Proper Formin Localizationmentioning
confidence: 99%
“…Thus, loss of Dma proteins does not seem to affect the whole polarisome. We previously showed that dma1D dma2D mutant cells are defective in the recruitment to the bud neck of the Elm1 kinase (Merlini et al 2012), which in turn is involved in septin organization, timely mitotic entry, and the checkpoint responding to spindle mispositioning (Sreenivasan and Kellogg 1999;Bouquin et al 2000;Thomas et al 2003;Gladfelter et al 2004;Caydasi et al 2010;Moore et al 2010). Artificial tethering of Elm1 to the bud neck by the Bni4-Elm1D420 chimeric protein (Moore et al 2010) significantly rescued the septin and spindle position defects of dma1D dma2D cells (Merlini et al 2012).…”
Section: Dma1 and Dma2 Are Required For Proper Formin Localizationmentioning
confidence: 99%
“…Gene deletions and epitope tagging were performed using PCR-based methods (Janke et al, 2004). Yeast growth conditions and synchronizations were done as described (Caydasi et al, 2010;Meitinger et al, 2010;Sherman, 1991). Primary antibodies were mouse anti-HIS, anti-PSTAIRE (recognizes Cdk1), antitubulin (Tub1), anti-HA (clone 12CA5, Sigma); rabbit anti-GFP, anti-Clb2, guinea-pig anti-Sic1, goat anti-GST (GE Healthcare), and sheep anti-Cdc14 (a gift from E. Schiebel, ZMBH, Germany).…”
Section: Reagents and Growth Conditionsmentioning
confidence: 99%
“…Kin4 itself is regulated at multiple levels. For example, phosphorylation by the protein kinase Elm1 is critical for kinase activity, whereas the protein phosphatase 2A bound to its targeting subunit Rts1 regulates Kin4 localization (10)(11)(12).…”
mentioning
confidence: 99%